Latin American Microfinancing Models: An Experience for Social Inclusion and Development - Perossa, Mario Luis; Gigler, Santiago (Cooperativismo & Desarrollo, 2015)
Introduction: In Latin America, micro-finance institutions have been responsible for leveraging small loans to millions of individuals to finance working capital and investments in small machinery. The objective of the work is to show the results that microfinance has on improving indicators for poverty and growth of the economy. Methodology: For the quantitative analysis, data were used on poverty, growth in countries according to their gnp, the savings rate and the growth of companies among other indicators in Latin American countries, which were then correlated with each other to examine variables that could be locomotives or explicative of the decrease in poverty rates. Results: After analyzing the correlation between the different variables, a strong relationship was found between the increase in the average amounts awarded and the decrease in the poverty rate; the strengthening of the microcredit market and its relationship to poverty in the countries that were analyzed was shown. Conclusions: Microfinance became a powerful tool in the fight against poverty in the countries where it was practiced, respecting the human dignity of those individuals who suffer from economic and social exclusion.